FAKTOR PENYEBAB DAN IMPLIKASI HUKUM MALAPRAKTIK MEDIS SERTA UPAYA PERLINDUNGAN HUKUM BAGI PASIEN DAN TENAGA MEDIS - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
Medical malpractice is one of the critical issues in Indonesia's healthcare system, significantly impacting patient safety and the security of the medical profession. This study aims to analyse the factors causing medical malpractice, its legal implications, and the effectiveness of legal protection measures for patients and medical personnel. The causes of medical malpractice include negligence, lack of competence, communication failure, inadequate facilities and infrastructure, and weak institutional oversight. The legal implications of medical malpractice encompass civil, criminal, and administrative liability, which often create legal uncertainty for both patients and healthcare professionals. Legal protection measures have been regulated in various regulations, but their implementation still faces challenges, such as the difficulty of proving negligence, low legal literacy among the public, and the ambiguity of the definition of medical malpractice. This study recommends strengthening the supervision system, harmonising regulations, and providing balanced legal education to ensure justice and legal certainty in the handling of medical malpractice cases in Indonesia.